SPATIAL DISTRIBUTION OF AVAILABLE NUTRIENTS IN THE POTATO GROWING AREAS OF BANASKANTHA DISTRICT OF GUJARAT - Kumar, Mahesh; Panwar, N R; Pandey, C B; Jatav, M K (Potato Journal, 2016)
A study on spatial variability in available soil nutrient i.e organic carbon (OC), available P, K and DTPA extractable micronutrients (Zn, Fe, Cu, and Mn) was carried out during 2011-2012. One hundred ten geo-referenced surface soil samples were collected from potato growing areas of Deesa tehsil of Banaskantha district (Gujarat). The maps showing the spatial variability of macro and micronutrients were generated using GIS software (Arc GIS-9.3). The organic carbon (OC) ranged from 0.18 to 0.80% with mean value 0.38%. About 30% samples rated high, 52% medium and 18% low in available phosphorus. While 77% samples were rated low, 15% medium and 8% high in available K. With respect to micronutrients, 40, 32 and 7% soil samples were found deficient in zinc, iron and copper, respectively. The corresponding values for different nutrients/parameters like OC, P, K, Fe, Zn, Mn, Cu and pH were linked with the respective sampling points and interpolation map for each nutrient was generated in GIS using IDW technique. The map on spatial variability of OC showed that 94.25 and 5.75 per cent area was in the range of 0.10-0.50% and >0.50% respectively. About 65.10% area was medium in available phosphorus and 27.30% area was high in available phosphorus whereas, 91.34% area was deficient in available K. Similarly 34.0, 29.8 and 3.3% area was classified as deficient in Zn, Fe and Cu, respectively. These spatial variability maps clearly showed the specific locales of the pockets where attention is required with respect to management of macro and micronutrients.